Loss of FAM111B protease mutated in hereditary fibrosing poikiloderma negatively regulates telomere length - Kliszczak, Maciej; Moralli, Daniela; Jankowska, Julia D.; Bryjka, Paulina; Subha Meem, Lamia; Goncalves, Tomas; Hester, Svenja S.; Fischer, Roman; Clynes, David; Green, Catherine M. (Frontiers in Cell and Developmental Biology, 2023)
Hereditary fibrosing poikiloderma (HFP) is a rare human dominant negative disorder caused by mutations in the FAM111B gene that encodes a nuclear trypsin-like serine protease. HFP patients present with symptoms including skin abnormalities, tendon contractures, myopathy and lung fibrosis. We characterized the cellular roles of human FAM111B using U2OS and MCF7 cell lines and report here that the protease interacts with components of the nuclear pore complex. Loss of FAM111B expression resulted in abnormal nuclear shape and reduced telomeric DNA content suggesting that FAM111B protease is required for normal telomere length; we show that this function is independent of telomerase or recombination driven telomere extension. Even though FAM111B-deficient cells were proficient in DNA repair, they showed hallmarks of genomic instability such as increased levels of micronuclei and ultra-fine DNA bridges. When mutated as in HFP, FAM111B was more frequently localized to the nuclear envelope, suggesting that accumulation of the mutated protease at the nuclear periphery may drive the disease pathology.